(untitled) (Fiep Bulletin - online, 2012)
Introduction: The practice of regular physical activity promotes important changes in cardiovascular performance,and produce changes in anthropometric parameters and body composition. Objective: To evaluate changes in anthropometricand cardiovascular adjustments adolescents aged 14 to 18 years, of both sexes, submitted to the handball training of 12 weeks.Methods: The study included 24 adolescents, 11 boys and 13 girls. We evaluated height, weight, body mass index (BMI), bodycomposition and cardiovascular parameters (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterialpressure (MAP) and double product (DP) before and after the period of 12 weeks of training handball. Results: There was asignificant increase (p <0.05) in boys’ height with no change in girls. There was a significant decrease (p <0.05) for BMI of boys,while girls increase was observed (p <0.05). There was no change in body composition in terms of percentage of fat and leanmass. In the pre-training period, we observed a significant increase (p <0.05) in the 5th minute after exercise in DBP and MAP infemales. In the post-training increased values were observed (p <0.05) in the 5th minute post-exercise HR, SBP, DBP, MBP andDP in girls. After 12 weeks, increased (p <0.05) in the 5th minute post-exercise HR and DBP and HR and DP in the 10th minuteafter exercise in boys. Conclusion: The training for handball 12 weeks promoted anthropometric changes, and generatecardiovascular adaptations in the adolescents studied